Immune-metabolic crosstalk in HNSCC: mechanisms and therapeutic opportunities - Qin, Xiyuan; Wu, Hui; Pan, Jiaqi; Kang, Kai; Shi, Yujie; Bu, Shoushan (Frontiers in Oncology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a prevalent malignancy, characterized by metabolic reprogramming. This reprogramming creates an acidic and hypoxic environment within tumor cells to adapt to metabolic changes. Experimental data indicate that in HNSCC, the metabolic reprogramming of tumor cells regulates immune cells via metabolites or signaling pathways, thereby promoting cancer progression or immune evasion. This article reviews the metabolic reprogramming in HNSCC, including glucose, fatty acids, amino acids, and nucleotide metabolism. These metabolic pathways play crucial roles in the proliferation, differentiation, and effector functions of immune cells, and influence immunosuppressive checkpoints. Additionally, this review explores the potential relationships between metabolic reprogramming, tumor immunity, and related treatments. Thus, targeting metabolic reprogramming and interactions between immune cells may help overcome therapeutic resistance in HNSCC patients.